Approximate Averaged Synthesis of the Problem of Optimal Control for a Parabolic Equation - Kapustyan, O. A.; Sukretna, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
For a problem of optimal control for a parabolic equation, in the case of bounded control, we construct and justify an approximate averaged control in the form of feedback.